1952
DOI: 10.2134/agronj1952.00021962004400110006x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Differential Clipping on Growth and Development of Seedling Grasses and Legumes1

Abstract: T HE need for proper management of forage species begins at the time of seeding and continues throughout the life of the plant. The early development of seedlings, which has a direct bearing on ultimate stands and production, is influenced to a considerable extent by time and frequency of defoliation. Very little detailed information is available on the development of young perennial grass and legume plants. Less work has been done to determine the effects of clipping on root development than on top growth. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1958
1958
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…Frequently and heavy clipping has a greater reducing effect on root development than above ground production (Carter andLaw 1948, Tosun 1971). These results also agree with Wagner (1952) who found that although root systems have been studied less intensively than tops, there is some evidence that the roots of forage species may be more seriously affected than the tops by certain grazing and clipping practises.…”
Section: Comparison With Control Plantssupporting
confidence: 91%
See 3 more Smart Citations
“…Frequently and heavy clipping has a greater reducing effect on root development than above ground production (Carter andLaw 1948, Tosun 1971). These results also agree with Wagner (1952) who found that although root systems have been studied less intensively than tops, there is some evidence that the roots of forage species may be more seriously affected than the tops by certain grazing and clipping practises.…”
Section: Comparison With Control Plantssupporting
confidence: 91%
“…Plants cut to 2.5 cm had the lowest tiller number. Wagner (1952) and Tükel et al (1996) also found that lower clipping heights decreases the number of tiller. The other 3 cutting treatments fell within the same range for tiller number.…”
Section: Tiller Numbermentioning
confidence: 92%
See 2 more Smart Citations
“…Particularly surprising was the low weight of recoverable clover root, due in part to errors of identification, though all tap-roots were recovered. In this connection it is interesting to note the low root/top ratio of clover, 1 ; 4 as compared with 1 : 0-4--0-8 for grass; this ratio is possibly a factor of great importance in resistance to drought and to elimination under adverse conditions (27).…”
Section: Chemical Analysismentioning
confidence: 97%